Phytocorrection of Gastrointestinal Tract Structural Changes Caused by the Use of 6-Mercaptopurine - YA. G. Razuvaeva; S. M. Nikolaev; A. O. Zandanov; YU. N. Sandanova; L. B. Buraeva (Антибиотики и Химиотерапия, 2020)
It was shown that the course use of Ventrofit, a complex plant remedy, normalized the structural and functional integrity of the stomach and thin intestine mucous membranes damaged by the use of 6-mercaptopurine.